Acetyl-CoA carboxylase 1-dependent protein acetylation controls breast cancer metastasis and recurrence - Rios Garcia, Marcos; Singhal, Mahak; Augustin, Hellmut; Nawroth, Peter Paul; Herzig, Stephan; Berriel Diaz, Mauricio (Cell metabolism, 2017)
Summary: Breast tumor recurrence and metastasis represent the main causes of cancer-related death in women, and treatments are still lacking. Here, we define the lipogenic enzyme acetyl-CoA carboxylase (ACC) 1 as a key player in breast cancer metastasis. ACC1 phosphorylation was increased in invading cells both in murine and human breast cancer, serving as a point of convergence for leptin and transforming growth factor (TGF) β signaling. ACC1 phosphorylation was mediated by TGFβ-activated kinase (TAK) 1, and ACC1 inhibition was indispensable for the elevation of cellular acetyl-CoA, the subsequent increase in Smad2 transcription factor acetylation and activation, and ultimately epithelial-mesenchymal transition and metastasis induction. ACC1 deficiency worsened tumor recurrence upon primary tumor resection in mice, and ACC1 phosphorylation levels correlated with metastatic potential in breast and lung cancer patients. Given the demonstrated effectiveness of anti-leptin receptor antibody treatment in halting ACC1-dependent tumor invasiveness, our work defines a “metabolocentric” approach in metastatic breast cancer therapy.
Available online 19 October 2017
Gesehen am 20.06.2018